Commentary: Responsibility (LEARNing Landscapes, 2009)
In this commentary, I argue that the current emphasis on accountability has overshadowed and weakened the far deeper concept of responsibility, and I ask readers to reflect on the scope and significance of teachers’ responsibilities. Accountability, defined too narrowly, demeans the work of teachers and may even invite corruption. In contrast, a serious look at responsibility leaves us in some awe at the breadth and importance of the work we undertake as teachers.
Keywords: curriculum; accountability; responsibility; teacher